Učinkovitost klinične supervizije na zadovoljstvo na delovnem mestu pri zaposlenih v zdravstveni neg - Trajbarič, Tamara (Obzornik zdravstvene nege, 2025)
Introduction: Nursing personnelexperience numerous mental, emotional, and physical stresses, which affect their job satisfaction. Occupational stress often arises from various work challenges and represents a global concern. The purpose of this literature review was to examine the effectiveness of clinical supervision on maintaining job satisfaction among nursing personnel.Methods: We utilised a descriptive approach that involved analysis, compilation, comparison, and synthesis of the literature. We searched for scientific literature in international databases such as PubMed, CINAHL Ultimate, Cochrane Library, and Web of Science in November 2024. Our final analysis included studies employing quantitative and qualitative methodologies, as well as systematic literature reviews in English, relevant to the research topic and conducted within the specified time frame. We evaluated the studies using a hierarchy of evidence, classified them by level, presented them in an evaluation table, and summarised the results in a synthesis table.Results: Our literature search yielded a total of 106 results, from which we included four original scientific articles and three literature reviews in the final analysis. One article was classified at the third level of the evidence hierarchy, one at the fourth level, one at the fifth level, one at the sixth level, and three articles at the seventh level. The results of our review show that clinical supervision positively affects healthcare professionals and significantly contributes to maintaining and improving job satisfaction.Discussion and conclusion: Although clinical supervision in nursing is not widely applied, it contributes significantly to maintaining and improving job satisfaction. We identified methodological shortcomings and other limitations such as the absence of a control group, small sample sizes, and bias. This literature review allows for a better understanding of the effects of supervision on nursing personneland helps identify gaps in existing knowledge. It can also influence curricula and educational programmes and serve as a basis for formulating policies that support effective supervisory practices and contribute to improving working conditions for nursing personnel.
Keywords: medicinske sestra; nurses; podpora; profesionalni razvoj; professional development; support